2021
DOI: 10.1155/2021/5574125
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and Verification of the Relationship between Ablation Index and Baseline Impedance

Abstract: Objective. To explore the quantitative adjustment of ablation index (AI) under different baseline impedance to achieve similar lesion dimensions. Methods. (1) Keeping the AIs relatively constant, the lesion dimensions in different baseline impedances were studied. (2) According to Joule's law, Q = I2RT, keeping the current (I) unchanged, the powers corresponding to different baseline impedances can be obtained. Under different baseline impedances and corresponding powers, the swine hearts were ablated for 30 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
3
1
0
Order By: Relevance
“…Consistent with the results of previous studies, 6,7,10,11 using various statical approaches, our ex vivo experiments progressively demonstrated that at similar AI values, baseline impedance exhibited a strong negative linear correlation with lesion dimensions, particularly lesion depth. Namely, ablation at lower baseline impedance resulted in larger lesion dimensions created by the same level of AI, which could be explained by a simple linear formula, albeit necessitating further investigation under other conditions.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with the results of previous studies, 6,7,10,11 using various statical approaches, our ex vivo experiments progressively demonstrated that at similar AI values, baseline impedance exhibited a strong negative linear correlation with lesion dimensions, particularly lesion depth. Namely, ablation at lower baseline impedance resulted in larger lesion dimensions created by the same level of AI, which could be explained by a simple linear formula, albeit necessitating further investigation under other conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the results of previous studies, 6,7,10,11 also reported a similar conclusion that impedance could influence ablation lesions, however, the impedance values in their experiment were distinctly lower than ours, which were more consistent with the real clinical practice. In addition, our study has revealed a threshold impedance-150 Ω, over which the predictive accuracy of AI seems to be compromised, given that the AI formula prospectively predicted lesion depth with high accuracy of ±1 mm in the context of AI-guided ablation.…”
Section: Impact Of Baseline Impedance On Ablation Lesionssupporting
confidence: 92%
See 2 more Smart Citations